Evaluation of Farmers’ and Vendors’ Perceptions and Knowledge Levels Regarding Product Safety and Pesticide Management Practices in Babul Makmur, Bukit Tusam, and Semadam Subdistricts, Southeast Aceh Regency - Ramut, Anuar; Vrand Apalon, Leo; Asrul, Asrul; Sibuea, Barita; Sasmitro Maha, Juandi; Maharani, Aulia; Murniati, Murniati (JALOW | Journal of Agribusiness and Local Wisdom, 2026)
Pesticide utilization plays a pivotal role in sustaining the continuity of agricultural commodity supply chains by mitigating potential yield losses attributable to pest and disease infestations. This study aims to examine the perceptions and knowledge levels of farmers and pesticide distributors in Babul Makmur, Bukit Tusam, and Semadam Sub-districts, Southeast Aceh Regency, Indonesia. The research was conducted from October to November 2025 using a descriptive survey approach based on structured interviews with questionnaire instruments encompassing indicators of perception, knowledge level, and pesticide use practices. Respondents comprised farmers as end-users and pesticide vendors as distribution agents. The data collected included respondent characteristics, types of pesticides utilized or marketed, dosage and application frequency, and comprehension of safety-related aspects. Descriptive analytical techniques were employed to identify prevailing trends in perception and knowledge among respondents. The findings indicate that although farmers and pesticide distributors demonstrate relatively high levels of knowledge and normative awareness regarding pesticide safety, the consistency of technical and administrative practices has not been fully institutionalized. Strengthening regulatory oversight, ensuring continuous educational interventions, and integrating distribution governance mechanisms are therefore essential prerequisites to safeguard safety standards, enhance accountability, and promote the sustainability of agricultural systems.